Gerold Prauss’s critique of cognition taken as reflection - Kubalica, Tomasz (Folia Philosophica, 2012)
The paper deals with Gerold Prauss’s critique of cognition taken as reflection of the surrounding reality in the consciousness of the agent (Abbildtheorie). The results of his critique are similar to the standpoint presented earlier by Neo-Kantians (Rickert, Cassirer). Prauss’s original contribution to the debate on theory of reflection consists in distinction between materialistic and non-materialistic theories of reflection, as well as in his argumentation basing on the notion of clarity (Deutlichkeit).